Analysis of Partnership-Based Cocoa Farming Development in Gunung Maria Village - Dongoran, Ranah santri; Muhammad Ikhsan Harahap; Purnama Ramadani Silalahi (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to analyze the development strategy Partnership-based cocoa farming in Gunung Maria Village, North Padang Lawas Regency. Cocoa is a leading sector with a strategic role in supporting the rural economy and significant potential. for both domestic and export markets. The research uses in-depth interview approach, and SWOT analysis (Strengths, Weaknesses, Opportunities, Threats, qualitative descriptive through field observation). The results of the analysis show that Gunung Maria Village has strengths in the form of abundant natural resources, strong partnerships, and farmer skills, as well as Opportunities such as increasing market demand and government support remain challenging. However, major challenges remain in the form of limited capital, access to technology, and road infrastructure. The SWOT mapping results place the village in Quadrant I, which is an aggressive strategy, which recommends leveraging internal strengths to achieve strategic objectives. seize external opportunities. The proposed strategy includes farmer training, product diversification, institutional strengthening, and the use of digital technology and export partnerships. These findings are expected to serve as a strategic reference in designing policies for sustainable agricultural development and improving the welfare of cocoa farmers.